Bilateral Rostral Mandibulectomy for the Management of Oral Tumor in Dogs: A Report of Two Cases - Reddy, Puli Vishnu Vardhan; Shafiuzama, Mohammed; Simon, Shiju; Raj, Pushkin; Ratnam, Thenmozhi; Sagare, Rajat (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
eoplasia in the oral cavity is the fourth most common site, accounting for about 5% of all malignant tumors detected in dogs and 7% in cats (Fossum et al., 2002). Bilateral rostral mandibulectomy involves the excision of a portion of the rostral aspect of both mandibles (Lantz 2012). The primary reason for performing a bilateral rostral mandibulectomy in dogs is to surgically remove benign or malignant oral tumors that extend across the midline rostral to the mandibular first premolar teeth (Smithson and Taney 2009). Although bilateral rostral mandibulectomy leads to mandibular prognathism, the cosmetic result and prehension and mastication functions are generally excellent (Salisbury 2003). This document presents a successful bilateral rostral mandibulectomy in two dogs with oral tumors without mandibular fixation and with cosmetic reconstruction of the lower lip without tension.